Alternative Mechanical Evaluation Method for Ceramic Hip Joint Implants Utilizing Finite Element Analysis under in vivo-like Conditions - Sungmin HAN; Jun-Uk CHU; Kang-Il SONG; Sunghee PARK; Jea Bong CHOI; Jong Woong PARK; Kuiwon CHOI; Inchan YOUN (Journal of Biomechanical Science and Engineering, 2012)
This study proposes an alternative mechanical simulation protocol for ceramic femoral heads under in vivo-like conditions. A 3D pelvis model is obtained from CT images and the finite elements of the implanted models are validated based on Kwong's experimental results. The stress distribution of nine different femoral head models is then compared when using the conventional proof test (standard ISO 7206-10) and proposed test protocol (postoperative models). Both test methods show a decrease in the maximum stress when increasing the size of the femoral head and bore depth. However, for the stress distribution, the postoperative models reveal a concentration on the superior inner region of femoral head cranial, while the proof test shows an axisymmetric shape in the tangential direction. As a non-uniformed stress distribution increases the probability of fracture, the mechanical testing of ceramic femoral heads should be considered under in vivo-like conditions in order to improve the mechanical reliability of the joint. Thus, the current results show the necessity and viability of an alternative mechanical evaluation method for ceramic hip implants.